Trends in Azole Resistance in Aspergillus fumigatus, the Netherlands, 1994–2016 - Jochem B. Buil; Eveline Snelders; Laura Bedin Denardi; Willem J.G. Melchers; Paul E. Verweij (Emerging Infectious Diseases, 2019)
We investigated azole resistance in Aspergillus fumigatus in a tertiary reference hospital in the Netherlands during 1994–2016. The 5-year patient-adjusted proportion of resistance increased from 0.79% for 1996–2001 to 4.25% for 2002–2006, 7.17% for 2007–2011, and 7.04% for 2012–2016. However, we observed substantial variation between years.